Essays in applied political economics - Tavares, Rafael Alves de Albuquerque (2021)
This doctoral dissertation consists of three independent essays, divided by chapters. In the first chapter, I examine the effects of banning corporate contributions to electoral campaigns. Using a difference-in-differences design in the suitable setting of the 2015 reform in Brazil that prohibited donations from companies, I find that banning corporate contributions led candidates to substitute the funding sources to finance campaigns. In particular, candidates relied on self-contribution. The ban also affected the pool of candidates by increasing the number of candidates running for office and attracting wealthier candidates. In terms of political selection for office, the ban led wealthier candidates to become mayors. Another interesting finding is that for municipalities with open seats the effect of favoring wealthier candidates is larger. These results suggest that even though the 2015 reform was aimed at reducing the role of money in elections, leakages such as the removal of specific limits to self-contribution can maintain the status quo of a few sources of \"big money\" setting the stage for successful candidacies. In the second chapter, I answer the following question: does the federal government prioritize its local allies on the provision of public resources? Using a regression discontinuity design in close elections and data of the Projeto Mais Médicos para o Brasil (PMM) - a program from the Brazilian Ministry of Health that targets the provision of basic health services and the increase of local medical density by transferring professionals to the Brazilian municipalities - this chapter assesses the impact of the political alignment between federal and local governments on the number of physicians transferred to municipalities and the municipalities\' probability of participation. The results suggest that the federal government does not prioritize same-party municipalities nor penalizes the ones governed by the opposition parties. I show that this null effect remains across municipalities with different levels of medical density and different population sizes. One explanation for these results is that with the \"branded\" nature of PMM and the wide media coverage of the program, the electoral credit for PMM ended going to the federal government and, hence, the party heading local governments would not be a critical factor for the distribution of doctors across municipalities. In the third chapter, I provide answers to the following question: are supporters of winning coalitions in local elections over-represented among beneficiaries of Minha Casa Minha Vida Program? Since 2009, suspicions have arisen about the lack of transparency in the selection of beneficiaries by city halls and about a potential political favoring of groups in the waiting list for housing. Using a Regression Discontinuity (RD) model on the margin of victory in municipal mayoral elections, this chapter investigates whether party members and campaign donors are selected more often in the program when supporting winning candidates. The results suggest that there is no such political favoring. Among the reasons for finding such null results are the possibility of mayors favoring indirect allies, or the difficulty of taking back homes from beneficiaries once granted, which substantially reduces the mayor\'s bargaining power. In addition, it is possible that the transparent selection of candidates is more frequent exactly in municipalities with high electoral competition and, therefore, with narrowly defined elections. In this case, the use of RD on the margin of victory could not elicit the effect of political favoring.